TINGKAT KEBERHASILAN INSEMINASI BUATAN MENGGUNAKAN SEMEN BEKU SEXING SAPI SIMMENTAL DI DESA KARANG BARU KECAMATAN DATUK TANAH DATAR KABUPATEN BATU BARA - Ridho Sahardi Berutu; Media Agus Kurniawan (Bajang Institute, 2025)
This study aims to determine the success rate of artificial insemination using frozen semen sexing Simmental cattle in Karang Baru village, Datuk Tanah Datar subdistrict, Batubara district, where there are 40 breeders with a population of 100 breeds of various breeds with a research sample of 20 breeder cows owned by 15 breeders are determined based on the Slovin formula approach with 3 parameters that determine success, namely, Non Return Rate (NRR), Service Per Conception (S/C), and Conception Rate (CR), then after carrying out the insemination process and pregnancy detection and re-data collection related to the success of insemination, data was produced based on research parameters, namely, NRR 70%, S/C 70%, and CR 1.3, so it can be concluded that the implementation of artificial insemination using frozen sexing semen from Simmental cattle has a high success rate based on the parameters that are also included. influences several success factors, namely the skill of the inseminator and the quality of the cement used.